Total Quality Management as a Tool for Decision Making - Sabur, Md. Abdus (Asian Business Review, 2013)
TQM means keeping the organization running smoothly with continuous input from our owners/customers. The major components of TQM are quality information, rewards for results, cooperation, secured jobs, fairness, equitable compensation, employees ownership stake etc the guiding principles are customer satisfaction safety, elimination of errors and defects, continuous improvement, employee empowerment etc The major constraints are lack of top management support, commitment, over dependence on computerized quality control, no market research, management by fear etc . JEL Classification Code: L15